Good Worker Health and Hygiene Practices: Evaluation and Importance in GAPs and GMPs - Melissa Holmes-Pearce; Mark Ritenour; Amy Simonne; Jeff Brecht; Steve Sargent; Keith Schneider (EDIS)
With increased consumption of fresh produce, the number of foodborne illnesses associated with fresh produce has also increased. Young children, the elderly, and people with immuno-compromising conditions such as HIV, AIDS, and cancer run even greater risk of serious illness or death related to contaminated foods. Therefore, it is now more important than ever that everyone involved in handling food uses recommended sanitation practices. Regardless if one works in the field, a packinghouse, a warehouse, on the loading dock, at a grocery store, or in a restaurant, good practices that assure food safety start at home and continue into the workplace. Always remember that the food products you handle MUST be safe to consume when they leave your care; your job depends on it. This document is FCS8766, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication: December 2004.